2019
DOI: 10.1038/s41408-019-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of isatuximab monotherapy in the treatment of refractory multiple myeloma

Abstract: This phase I dose-escalation/expansion study evaluated isatuximab (anti-CD38 monoclonal antibody) monotherapy in patients with relapsed/refractory multiple myeloma (RRMM). Patients progressing on or after standard therapy received intravenous isatuximab (weekly [QW] or every 2 weeks [Q2W]). The primary objective was to determine the maximum tolerated dose (MTD) of isatuximab. Overall, 84 patients received ≥ 1 dose of isatuximab. The MTD was not reached; no cumulative adverse reactions were noted. The most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
112
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 29 publications
15
112
3
Order By: Relevance
“…Isatuximab has been investigated as monotherapy for the treatment of RRMM in a phase 1/2 trial (ClinicalTrials.gov, NCT01084252) [34][35][36]. Martin and colleagues [35] evaluated isatuximab as monotherapy against RRMM in a phase 1 dose-escalation/expansion study, with the goal to determine the maximum tolerated dose of isatuximab. Overall, 84 patients with RRMM progressing on or after standard therapy received 0.0001-20 mg/kg of isatuximab intravenously (IV) weekly or every 2 weeks.…”
Section: Isatuximab Monotherapy Activity In MMmentioning
confidence: 99%
“…Isatuximab has been investigated as monotherapy for the treatment of RRMM in a phase 1/2 trial (ClinicalTrials.gov, NCT01084252) [34][35][36]. Martin and colleagues [35] evaluated isatuximab as monotherapy against RRMM in a phase 1 dose-escalation/expansion study, with the goal to determine the maximum tolerated dose of isatuximab. Overall, 84 patients with RRMM progressing on or after standard therapy received 0.0001-20 mg/kg of isatuximab intravenously (IV) weekly or every 2 weeks.…”
Section: Isatuximab Monotherapy Activity In MMmentioning
confidence: 99%
“…The other clinical grade anti-CD38 mAb, Isatuximab, is a human IgG1κ mAb under early clinical trials, in which it has shown meaningful anti-tumor activity [47,48]. Compared to Daratumumab, Isatuximab displays a stronger action of direct cell killing independent on cross-linking.…”
Section: Effects Of Cd38-directed Immunotherapy On Immune Cell Levelsmentioning
confidence: 99%
“…A phase 1 dose-escalation/expansion study first evaluated isatuximab monotherapy (20 mg/kg the highest dose tested QW or Q2 W) in 84 patients with RRMM (NCT01084252) [60]. Maximum-tolerated dose (MTD) was not reached.…”
Section: Isatuximabmentioning
confidence: 99%